GARNISH AND PLATING TRAINING FOR PKK MOTHERS OF KEUBON BARO VILLAGE, SIMPANG KRAMAT SUB DISTRICT,ACEH UTARA: PELATIHAN MEMBUAT GARNISH DAN PLATING UNTUK IBU-IBU PKK GAMPONG KEUBON BARO, KECAMATAN SIMPANG KRAMAT, ACEH UTARA - Idaryani, Idaryani; Fidyati, Fidyati (PT. ROCE WISDOM ACEH, 2025)
TThe implementation team conducted this community service activity in the form of a training sessionon garnish making and plating for the PKK mothers of Keubon Baro Village, Simpang KramatSubdistrict, North Aceh. Garnishing is the process of enhancing the appeal and aesthetics of a dish,while plating refers to the arrangement and decoration of food to achieve a perfect presentation. PKKmothers are influential women in the community, typically referring to a group of women engaged invarious positive activities. These activities include Small and Medium Enterprises (SMEs), religiousstudy groups, seminars, health programs, family planning, and other initiatives, such as foodpresentations, which are one of the PKK's key functions in the food sector. The lack of understandingof simple food arrangement techniques among PKK mothers became an interesting issue, prompting the implementation team to plan this community service activity. The team from the Architecture StudyProgram partnered with the mothers of Keubon Baro Village to introduce and practice garnish andplating techniques. The service activity included the introduction of necessary tools, followed by cuttingand presentation techniques. The activity concluded with an appreciation session for the PKK mothers'group, who successfully created simple garnishes and plated dishes